Gender Issues And Islamic Family - Ernawati Ernawati; Erwan Baharudin (AIUA Journal of Islamic Education, 2019)
Islam is often considered discriminatory against women with the concept of polygamy, thalak, inheritance and women's testimony, the concept of mahram for women if they want to leave and even the concept of hijab is considered as symbols of restraint on women's freedom in the Islamic world. Where women in the family are considered not to have the same gender role as men. Here gender discourse cannot be separated from theological studies, because the position of women in religious thought is indeed placed as the second being, especially about the origin and function of the existence of both. The perpetuation of gender inequality widely in religion originates from the nature of religion itself or is derived from the understanding, interpretation and thought of religion which is not impossible to be influenced by patriarchal traditions and culture or other views. Therefore an understanding is needed to place the real role of women in the family according to the guidance of the teachings of Islam. The purpose of this study is to find out how Islamic teachings place the role and position of women in the family. This research is a descriptive analytical research design using conflict and feminist theory approaches, with the hope that there will be a deeper analysis of gender issues in the Islamic family more deeply.